ANALISIS PENGUKURAN RESIKO PADA PENYALURAN PEMBIAYAAN ANGGOTA KOPERASI MELALUI KOPERASI KARYAWAN (KOPKAR) SEBAGAI EXECUTING AGENT: STUDI KASUS PT. BANK MUAMALAT INDONESIA CABANG BOGOR - Pangestuti, Rinda Siaga (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
This study aims to measure the risk of distributing cooperative membersfinancing through Employee Cooperative (Kopkar) as executing agent at MuamalatBank Indonesia (BMI), Bogor branch. The contribution of this research lies in: 1)Strategy to overcome operational, credit, strategic, liquidity, and legal risks for thedistribution of cooperative member financing; 2) Analysis of expected loss andunexpected loss in member financing portfolio of cooperatives; 3) Analysis ofeconomic capital values that must be provided by BMI Bogor branch to coverunexpected loss; 4) The fit model analysis of CreditRisk+ in measuring the financingrisk of cooperative members using the Poisson distribution model. The dataprocessing method uses CreditRisk+ model based on Credit Suisse Financial Product(CFSB) framework. The financing product analyzed is the financing of cooperativemembers. The results of this study are: 1) Operational risk can be overcome byincreasing the fleet of office cars and the number of account officers. Credit risk canbe overcome by tightening the terms of the proposed financing. Strategic risk can beovercome by tightening control over the discipline of installment payments. Liquidityrisk can be overcome by limiting the number of loan accounts on the same mudharib.Legal risks can be overcome by backing up a cessie guarantee with fiducia guarantees;2) The expected value of loss in 2009 is 2,159,808,000 IDR and 2010-2011 is563,119,000 IDR. Unexpected loss value of loss 3,513,600,000 IDR in 2009 and1,054,100,000 IDR in 2010-2011; 3) The value of economic capital in 2009 amountedto 1,353,792,000 IDR and 490,981,000 IDR in the year of 2010-2011; 4) CreditRisk+model is suitable to measure unexpected loss in the financing of cooperative member.